Can oblique lateral interbody fusion (OLIF) create more lumbosacral lordosis in lumbar spine surgery than minimally invasive transforaminal interbody fusion (MIS-TLIF)? - Li, Jie; Chen, Yilei; Wu, Hao; Gan, Kaifeng; Bei, Dikai; Fan, Tengdi; Chen, Jian; Zhao, Fengdong; Chen, Binhui (Frontiers in Surgery, 2023)
Abstract Objective: To compare the differences in the correction effect for lumbosacral lordosis effect and clinical outcomes between OLIF with/without posterior pedicle screw fixation (PSF) and MIS-TLIF through a retrospective cohort study. Method: There were 98 consecutive patients originally enrolled for the study, but 15 patients were excluded due to intraoperative endplate injury and or osteotomy was performed for severe spinal deformity. UltimatelyThus, 83 patients were included in this study (36 males and 47 females, mean age 65.8 years) who underwent single to three-segment OLIF (including OLIF + PSF and OLIF Standalone) or MIS-TLIF surgery from 2016 to 2018. The operation time, blood bleeding and blood transfusion, fusion rate, complication, pre-and postoperative visual analogue scale (VAS), Oswestry Disability Index (ODI) were evaluated. In addition, radiological parameters including, lumbosacral lordosis (LL), fused segment lordosis (FSL), anterior disc height (ADH) and posterior disc height (PDH) were measured. The clinical outcomes, LL, FSL, ADH and PDH restored and were compared between the OLIF group, OLIF subgroups and MIS-TLIF group. Results The average operation time and intraoperative bleeding were significantly less in the OLIF group than in the MIS-TLIF group (163±68 vs 233±79 min, 116±148 vs 434±201 ml, P＜0.001). There was no statistically significant difference between the OLIF group and the MIS-TLIF group in VAS and ODI improvements, fusion rate, complication, LL and FSL correction (P＞0.05). The ADH and PDH increases in the OLIF group was were more than that in MIS-TLIF group (P＜0.001). The correction of LL was significantly more in the OLIF + PSF group than in the MIS-TLIF group (9.9±11.1 vs 4.2±6.1deg, P=0.034). Conclusion OLIF and MIS-TLIF are both safe and effective procedures, capable of restoring lumbosacral lordosis and disc height partly. Adding Combined with PSF, OLIF can acquire achieve a better correction effect of lumbosacral lordosis than MIS-TLIF.